Contralateral pulmonary metastases in lung cancer. Issue 1 (January 1974) - Onuigbo, Wilson I. B.
Abstract : Onuigbo, W. I. B. (1974). Thorax, 29, 132-133. Contralateral pulmonary metastases in lung cancer. It has long been known that lung cancer may attack many organs and yet spare the opposite lung. In 100 cases of this tumour studied at necropsy, only 22 showed contralateral pulmonary spread. Contralateral deposits are generally small and may be related to damaged tissues. Although tissue unsuitability is supposed to underlie the limitation of metastases in recipient organs, this does not apply to the contralateral lung. Since lung tissue is readily accessible to bloodborne cancer cells, research should be directed towards explaining the paradoxical paucity of the metastases.